The dynamics of international migration and settlement in Europe : a state of the art - Penninx, Rinus; Berger, Maria; Kraal, Karen (IMISCOE joint studies., 2006)
The first title in an international new series focusing on migration, integration and social cohesion in Europe post 1945.